2007
DOI: 10.1016/j.hrthm.2007.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Model of reentrant ventricular tachycardia based on infarct border zone geometry predicts reentrant circuit features as determined by activation mapping

Abstract: Background-Infarct border zone (IBZ) geometry likely affects inducibility and characteristics of postinfarction reentrant ventricular tachycardia, but the connection has not been established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
64
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(71 citation statements)
references
References 30 publications
7
64
0
Order By: Relevance
“…Several mathematical models exist that may be able to predict VT channels and successful ablation sites based on the infarct border zone geometry. 25 …”
Section: Supplementary Mri Substrate Characterization During Vt Ablationmentioning
confidence: 99%
“…Several mathematical models exist that may be able to predict VT channels and successful ablation sites based on the infarct border zone geometry. 25 …”
Section: Supplementary Mri Substrate Characterization During Vt Ablationmentioning
confidence: 99%
“…In contrast, regions of fast conduction coincided with areas of thicker border zones with minimal gradients. 1,16 Tachycardia-related slow-conducting channels have been identified within dense electroanatomic scar areas in the majority of patients with monomorphic VT after AMI. The mean length of these channels was 23Ϯ11 mm, and the mean cycle length of the channel-related VT was 365Ϯ77 ms, similar to the VT cycle length found in nonreperfused patients in our study.…”
Section: Arrhythmia and Electroanatomic Scarmentioning
confidence: 99%
“…Mapping studies have shown that reentry circuit locations and VT characteristics vary greatly among patients and are influenced by the 3-dimensional geometry of infarcted areas. [1][2][3] In animal models, the duration of coronary artery occlusion determines the size, transmurality, and geometry of myocardial fibrosis after AMI. 4,5 Thus, it seems likely that early reperfusion, which has become the standard treatment of AMI, will influence the nature of the VT substrate.…”
mentioning
confidence: 99%
“…1 Canine and swine models of experimental infarction can be useful to study the electrophysiological characteristics of this arrhythmia. [2][3][4] In a canine infarction model, the VT reentrant circuit often resides in the infarct border zone (IBZ), which is the thin region of surviving myocardium between the infarct rim and the epicardial surface. 2,5,6 For the canine infarction model, the IBZ is thinnest at the reentrant circuit isthmus location.…”
mentioning
confidence: 99%